Anti-fatigue effect of OM-X, fermented plant extract with lactic acid bacteria and bifidobacteria: A randomized, placebo-controlled, double-blind, comparative study - Takeshi Kaneko; Akinobu Miyata; Muneaki Takahata (Journal of Functional Foods, 2022)
The objective of this study is to elucidate how the OM-X made from many kinds of plants fermented using lactic acid bacteria (LAB) and bifidobacteria contributes to anti-fatigue. A randomized, placebo-controlled, double-blind, comparative study design was adopted. We investigated the effects of 12-week ingestion of the test food or placebo. Visual analogue scale (VAS) and Chalder fatigue scale (CFS) were examined to evaluate the feeling of fatigue, and diacron-reactive oxygen metabolites (d-ROMs) and Biological Antioxidant Potential (BAP) were measured to appraise comprehensive antioxidative ability. We also evaluated the safety of the food. As a result, significant differences between the two groups were detected in VAS and CFS. No safety-related matter occurred. It turned out that the ingestion of OM-X improved feelings of fatigue for healthy people with temporary fatigue. Additionally, there was no adverse effect by the ingestion of the food.